Pengaruh Kesadaran Siswa Terhadap Pentingnya Matematika dalam Karir di Era Digital dan Ekonomi Berbasis Pengetahuan - Khotna Sofiyah; Naswa Egi Nasution; Amisyah Amelia; Lisa Anjany Hutagalung (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Mathematics education in Indonesia faces significant challenges in raising students' awareness of the relevance of mathematics in daily life and the workforce, particularly in the digital era and knowledge-based economy. This study aims to assess the influence of students' awareness of the importance of mathematics in their future careers. Using a quantitative approach, the research collects data from students at various educational levels and analyzes their views on the relationship between mathematics and career development. The results show that students' awareness of the relevance of mathematics in careers, especially in technology, economics, and science, affects their interest and motivation to study mathematics. These findings indicate the importance of increasing awareness through more relevant and technology-based learning approaches to prepare students to face career challenges in the future.